SOUNDSCAPE IN TIMES OF CHANGE: EXPLORING THE IMPACT OF COVID-19 ON THE URBAN SOUNDSCAPE OF DIDOUCHE MOURAD STREET IN CONSTANTINE, ALGERIA - Asma Bensaada; Soumia Bouzaher; Amira Talbi (International Journal of Innovative Technologies in Social Science, 2024)
This research paper delves into the intricate relationship between soundscape, urban environments, and the impact of COVID-19, with a particular focus on Didouche Mourad street in Constantine, Algeria. The study aims to identify and emphasize the significance of this unique soundscape, both before and after the onset of the pandemic, by employing a multi-faceted research approach, combining site surveys, data collection tools, and an extensively administrated- questionnaire.To understand the perception and importance of the soundscape in the lives of the inhabitants, a questionnaire was administered to 159 residents in the area, exploring how their experiences and perceptions of the soundscape changed in the wake of the pandemic. The questionnaire covered aspects such as the emotional impact of soundscapes, the recognition of sound landmarks, and their evolving roles in creating a sense of place and identity.The survey results, along with the residents' perceptions and experiences, were considered to evaluate the changing importance of the soundscape within Didouche Mourad street in Constantine, Algeria, in the context of the COVID-19 pandemic.This research paper sheds light on the impact of COVID-19 on the often-neglected auditory dimension of urban landscapes. By investigating the soundscape of Didouche Mourad street in Constantine and juxtaposing it with its urban features before and after the pandemic, the study uncovers the intertwined relationship between sound and place and how it evolved in response to the public health crisis. The results contribute to a deeper understanding of the dynamic nature of soundscapes in shaping urban identity and provide valuable insights for urban planning, preservation, and the enhancement of the human experience within urban spaces during and after significant disruptions like the COVID-19 pandemic.